THE INFLUENCE OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IS MODERATE BY CAREER DEVELOPMENT AT THE REGIONAL TAX AND RETRIBUTION MANAGEMENT AGENCY OF MEDAN CITY - Widowati, Nidia; Arief Nasution, Aulia; Rifki Hafas, Hafriz (CV. Lafadz Jaya, 2024)
This research aims to determine the effect of motivation and job satisfaction on employee performance with career development as a moderating variable at the Medan City Regional Tax and Retribution Management Agency. This research design is moderated multiple linear regression analysis used as an analytical tool to find out how the influence between independent and dependent variables is moderated by the moderating variable. This research uses associative research with a quantitative approach. The population and sample in this research are the staff of the Medan City Regional Tax and Retribution Management Agency with a sample of 161 staff. The results of this study show that the variables of motivation and job satisfaction have a positive and significant influence on employee performance. For the career development variable which acts as a moderating variable, in this research the career development variable is able to significantly moderate the motivation and job satisfaction variables on employee performance.